Kualitas Hidup Penderita Karsinoma Serviks dengan Kemoterapi di RS Dr. Sardjito Yogyakarta - Sulistyowati, Yeni Nur; Widyawati, Widyawati; Aulawi, Khudazi (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2006)
Please refer to the file